John G. Aikin, A Digest of the Laws of the State of Alabama 201, § 1 (1822) - (:unkn) unknown (My University, 1822)
Prohibited hunting with fire at night-time. Punishable by a fine of fifty dollars. Only construed to "embrace persons hunting deer with a gun and fire at night."
Keywords: HUNTING REGULATION